The Impact of Adhesion Molecules on the In Vitro Culture and Differentiation of Stem Cells. Issue 2 (27th December 2017) - Abdal Dayem, Ahmed; Lee, Soobin; Y. Choi, Hye; Cho, Ssang‐Goo
Abstract: The term "cell adhesion" represents cell–cell interactions and the interaction between the cell and the extracellular matrix (ECM). These interactions are crucial for the development of the stem cells niche to determine stem cell shape. The ECM is considered as a natural niche for cell residence. Cell adhesion molecules (CAMs) enable cell–cell interactions and the interactions between the cell and ECM via various mechanisms, such as trans‐interaction and the heterophilic interactions. These interactions promote a broad spectrum of cell signaling that directly or indirectly modulates stem cell proliferation, self‐renewal property, adhesion, and multilineage differentiation. Over many years, animal‐derived feeder layers and culture components have been used for stem cell culture, which produces stem cells unsuitable for clinical applications in the regenerative medicine. This review briefly describes the stages of the development of stem cell culture toward a defined condition and the drawbacks of using animal‐derived culture components. Stem cell niche‐derived and ECM‐derived adhesion molecules and their detailed impact on stem cell adhesion and functions will be discussed. Efficient and novel adhesion molecules for stem cell culture and differentiation are needed for further large‐scale applications in tissue regeneration. Abstract : Cell adhesion molecules (CAMs) are derived from ECM or can be synesthetic peptides or polymers. The various types of CAMs and their impacts on stem cell functions, such as self‐renewal, proliferation, and differentiation is summarized. Interestingly, these CAMs can modulate several signalings pathways and transcription factors that mediate stem cells self‐renewal, proliferation, and differentiation. Moreover, this review describes how these CAMs could improve the quality of stem cell culture conditions and obviate the undefined as well as the animal‐derived culture components that hinder the application of the produced stem cells in the human regenerative medicine. This review incites the research groups to delve into the mechanisms of these CAMs in stem cell biology and further clinical application in the human regenerative medicine.